What Are The Most Effective Non-Pharmacological Interventions For Preventing Osteoporosis And Sarcopenia In Adults Over 65 Years Old? - Calista Giovani; Yudhi Hajianto Nugroho; Mutia Juliana (International Medical Journal Corp. Ltd, 2025)
Introduction: Osteoporosis and sarcopenia are prevalent conditions among older adults, particularly those over 65, leading to increased fracture risk and functional decline. Understanding effective non-pharmacological strategies for prevention is crucial as the global population ages. This study evaluates the efficacy of exercise and dietary modifications in preventing these conditions. Methods: This systematic review adhered to PRISMA guidelines, focusing on randomized controlled trials that evaluated non-pharmacological interventions in adults aged 65 and older. Eligible studies were screened for their focus on primary prevention, intervention type, and outcome measures related to bone mineral density, muscle mass, and physical performance. Results: A total of 39 studies were included, revealing that high-intensity resistance training significantly improved bone mineral density and muscle strength. Nutritional interventions, particularly protein supplementation, enhanced the effects of exercise on muscle mass and functional performance. Multicomponent exercise programs integrating balance, aerobic, and resistance training also showed positive outcomes in reducing fall risk. Discussion: The findings underscore the importance of structured exercise programs and dietary modifications in preventing osteoporosis and sarcopenia. Community-based interventions demonstrated higher adherence rates, while home-based programs offered flexibility for older adults. Conclusion: Non-pharmacological interventions, particularly high-intensity resistance training combined with dietary support, are effective strategies for preventing osteoporosis and sarcopenia in older adults. Future research should focus on enhancing long-term adherence to these interventions to improve health outcomes in this vulnerable population.